2021
DOI: 10.3389/fevo.2021.633634
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Diachronic Size Variation in Prehistoric Central Asian Cereal Grains

Abstract: The morphology of ancient cereal grains in Central Asia has been heavily discussed as an indicator of specific genetic variants, which are often linked to cultural factors or distinct routes of dispersal. In this paper, we present the largest currently existing database of barley (n = 631) and wheat (n = 349) measurements from Central Asia, obtained from two different periods at the Chap site (ca. 3,500 to 1,000 BC), located in the Tien Shan Mountains of Kyrgyzstan at 2,000 masl. The site is situated at the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…Furthermore, they asserted that the movement of domesticates from the northern Indian subcontinent into Kashmir where mountain environments may have driven a change in seed size owing to the weakening of summer and winter precipitation and lower water availability after ca. 2000 BCE (Lone et al, 2020;Shah et al, 2020;Spate et al, 2022a), as has been noted elsewhere in Central Asia (Motuzaite Matuzeviciute et al, 2021). Sharma et al (2020), based on a comprehensive account of macro-botanical remains and direct dates of food grains from Binjor, an Indus Valley (Harappan) site in northwestern India, revealed that the area was occupied by an agricultural society during the Early Phase (ca.…”
Section: Late Glacial Tomentioning
confidence: 70%
“…Furthermore, they asserted that the movement of domesticates from the northern Indian subcontinent into Kashmir where mountain environments may have driven a change in seed size owing to the weakening of summer and winter precipitation and lower water availability after ca. 2000 BCE (Lone et al, 2020;Shah et al, 2020;Spate et al, 2022a), as has been noted elsewhere in Central Asia (Motuzaite Matuzeviciute et al, 2021). Sharma et al (2020), based on a comprehensive account of macro-botanical remains and direct dates of food grains from Binjor, an Indus Valley (Harappan) site in northwestern India, revealed that the area was occupied by an agricultural society during the Early Phase (ca.…”
Section: Late Glacial Tomentioning
confidence: 70%
“…The plump and spherical nature of both barley and wheat grains in the assemblage, however, raises questions about the effect of local growing conditions (e.g., aridity, access to water) on the morphology of grain seeds. A consideration already highlighted by Miller (1999) and further built upon by others (e.g., Spengler, 2015;Matuzeviciute et al, 2021).…”
Section: Domesticated Grainsmentioning
confidence: 90%
“…However, systematic macrobotanical research at a handful of sites in the mountains of Central Asia over the past decade, combined with direct radiocarbon dating of carbonized seeds, indicates that the earliest pastoralist strategies there were accompanied by wheat, barley, and millet agriculture (Doumani et al, 2015;Frachetti et al, 2010;Yatoo et al, 2020;Zhou et al, 2020). Similar work has further revealed that Central Asian communities of the later Bronze Age and Iron Age (1000 cal ) cultivated an increasingly wide range of plant domesticates as people facilitated subsequent agricultural dispersals and adapted plants for cultivation in highland environments Motuzaite Matuzeviciute, Mir-Makhamad, & Spengler, 2021;Motuzaite Matuzeviciute, Mir-Makhamad, & Tabaldiev, 2021;Spengler et al, 2013Spengler et al, , 2014. Taken together, this research has greatly shifted our understanding of Central Asia, from a domain of nomadic pastoralists to a region with a compelling record for farming (Spengler et al, 2021).…”
Section: Introductionmentioning
confidence: 91%